DEVELOPING ENGLISH READING MATERIALS IN PROCEDURE TEXT FOR ELEVENTH GRADE STUDENTS OF CHEMICAL ANALYSIS AT SMK NEGERI 3 MEDAN - THESSALONICA A.R TAMBUNAN; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
The objective of this study is to develop the suitable and appropriate procedure text materials for reading skill, for Chemical Analysis program students. It was found that procedure text materials provided in the students’ textbook were not suitable and appropriate to the needs and interests of Chemical Analysis program students. This study is categorized into research and development (R&D). This study was conducted at SMK Negeri 3 Medan. The subject of this study was the eleventh grade students of Chemical Analysis program. The steps of this research were gathering information and data, analyzing data, developing materials, validating new materials by expert, revising materials and the final products. The result of the data were in the form of quantitative data obtained using questionnaire and qualitative in the open-ended questions. The developed reading material consisted of a unit. The texts were developed into three new suitable procedure text materials and about daily activity. Regarding understanding the generic structure of each text, comprehending text, completing sentences, filling in the blanks, answering question, arranging random sentences, choosing a title, matching the headings, vocabulary information, and true or false were appropriate. The developed reading materials were validated based on the suggestions of the teacher and the lecturer that selected as the experts. The average score of validation were 4, 45. It showed that the developed procedure materials were very good, suitable, appropriate and relevant with the students’ needs and interests.